A comprehensive review of bilirubin determination methods with special emphasis on biosensors. (February 2020) - Rawal, Rachna; Kharangarh, Poonam R.; Dawra, Sudhir; Tomar, Monika; Gupta, Vinay; Pundir, C.S.
Highlights: Bilirubin, is a tetrapyrrole yellow compound formed by catabolism of blood heme. This review describes advantages and disadvantages of various bilirubin methods. This review focuses on various types of bilirubin biosensors. It also compares analytical properties of various bilirubin biosensors. Abstract: Bilirubin, is a tetrapyrrole yellow coloured compound found in digestive juice. It is generated from degradation of hemoglobin (Hb). The normal range of total bilirubin in serum is 0.30–1.20 mg/dl. The elevated range of serum bilirubin is considered as biomarker for finding and therapeutic administration of many liver diseases. Various analytical methods for determination of bilirubin, including spectrophotometery, thin layer chromatography, fluorometry, capillary electrophoresis, high performance liquid chromatographic, polarography and chemiluminescence have been applied for clinical purposes. These conventional methods are tedious, time-consuming, and require costly equipments and skilled person to operate. To overcome these limitations, the most popular biosensing technology has been employed at a large scale. The present review describes the principle, advantages and disadvantages of different analytic methods for measurement of bilirubin with focusing on biosensors, including electrochemical, photo-electrochemical, piezoelectric, optical and luminescent biosensors in detail. The working conditions for optimum activity and shelf life of all bilirubin biosensors have been summarized & compared and their future perspectives are discussed.